Unpacking Taboo Words in Game Chats: A Content Analysis of MLBB Games - Habibillah, Putri Lira; Sagala, Rakhmat Wahyudin (Tamaddun Life, 2022)
This research attempted to explore the types of taboo expressions in the MLBB game chat and ascertain the reaction to the taboo words adopted in the MLBB game chat. The Qualitative Content Analysis Method was applied in this study. The researcher interviewed three MLBB game players and took screenshots of their in-game chat comments in order to gather the data. The results demonstrate that while not all MLBB players adopt the types of taboo language, there was one player who exclusively utilized it. The category with the greatest data is vulgar terms, with 32 words or 40% of the total; the second category is epithets and obscenity, with 22 words or 27.5% of the total; and the third category is profanity, with just 4 words or 5% of the total. Factors that contribute to players employing taboo words in MLBB games include their desire to draw attention, insult teammates or enemies, and provoke opponents to make the game exciting. Upon insulting and provoking their opponents, players feel relieved and pleased because their emotions were let out in the game. Subsequently, the findings have significant ramifications for enhancing learners' awareness of taboo language and contributing to the advancement of linguistic disciplines.